2018
DOI: 10.1002/mnfr.201700969
|View full text |Cite
|
Sign up to set email alerts
|

A Catechol‐Type Resveratrol Analog Manifests Antiangiogenic Action by Constructing an Efficient Catalytic Redox Cycle with Intracellular Copper Ions and NQO1

Abstract: This work provides further evidence that dietary catechols manifest antiangiogenic activity by virtue of their copper-dependent prooxidative instead of antioxidative role, and useful information for designing polyphenol-inspired angiogenesis inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…25 Accordingly, we have found that 3,4-DHS works as a copper-dependent pro-oxidant to activate Nrf2 signaling, 22 kills cancer cells selectively, 23 and inhibits angiogenesis. 24 Also, we have verified that elongating the conjugated link of 3,4-DHS is an effective strategy to improve its copper-dependent pro-oxidative ability, as exemplified by the catechol-type diphenylbutadiene (3,4-DHB, Scheme 1). 3,4-DHB has been identified as a more potent tyrosinase (a copper-containing enzyme)-dependent pro-oxidative cytotoxic agent 27 and chemosensitizer 28 against melanoma cells than 3,4-DHS.…”
Section: ■ Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…25 Accordingly, we have found that 3,4-DHS works as a copper-dependent pro-oxidant to activate Nrf2 signaling, 22 kills cancer cells selectively, 23 and inhibits angiogenesis. 24 Also, we have verified that elongating the conjugated link of 3,4-DHS is an effective strategy to improve its copper-dependent pro-oxidative ability, as exemplified by the catechol-type diphenylbutadiene (3,4-DHB, Scheme 1). 3,4-DHB has been identified as a more potent tyrosinase (a copper-containing enzyme)-dependent pro-oxidative cytotoxic agent 27 and chemosensitizer 28 against melanoma cells than 3,4-DHS.…”
Section: ■ Introductionmentioning
confidence: 71%
“…We have previously verified that intracellular copper-mediated oxidation of 3,4-DHS is a critic step for its ability to activate the Nrf2 signal 22 and inhibit angiogenesis. 24 It should be pointed out that intracellular free copper ions are maintained at very low levels, 35 but very low levels of them could efficaciously oxidize catechol-type molecules in a catalytic mode. Alternatively, catechol-type molecules are probably efficient substrates of copper-containing enzymes such as tyrosinase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations